The utility of routine endocervical curettage at the time of colposcopy for low-grade cytologic abnormalities to improve diagnosis of high-grade diseases - Chanakarn Suebthawinkul; Thitiwan Chaisuriyapun (The Royal Thai College of Obstetricians and Gynaecologists, 2016)
Objective:To determine the use of endocervical curettage(ECC) at the time of colposcopy for low-grade cytologic abnormalities to improve the diagnosis of high-grade diseases.Materials and methods: A prospective diagnostic study was conducted. We included women with low-grade cytologic abnormalities: low-grade squamous intraepithelial lesion (LSIL) who had undergone colposcopy at Chonburi Hospital between January 2014 to March 2015. Data collected were age, menopausal status, HIV status, parity, contraception, colposcopic findings and pathological report of biopsy and ECC.Main outcome measure: Primary outcome was the increasing rate of ECC in colposcopy for LSIL to detect high-grade lesion.Result: Eighty-seven women met criteria. Nine cases (10.3%) were ECC positive for high-grade lesion. Of these nine cases, seven cases were only ECC positive, resulting in 8.04% increased detection with ECC independently of biopsy, with a sensitivity of 20.0%, specificity of 91.91%, positive predictive value of 22.22% and negative predictive value of 89.74%. Therefore, twelve to thirteen ECCs needed to be performed to detect one case of high-grade diseases. Among post-menopausal women or women older than 40 years old, the sensitivity of ECC improved, with a sensitivity of 100% and 85% respectively.Conclusion: The increased detection rate of ECC to detect high-grade lesions in women who had low-grade cytological abnormalities in our study was 8.04%. Routine ECC at the time of colposcopy for LSIL in young women is debatable. However, the sensitivity of ECC was found to be increased in women aged over 40 and post-menopausal women. Therefore, ECC may be useful in older and post-menopausal women.